Survey of cassava brown streak disease and association of factors influencing its epidemics in smallholder cassava cropping systems of coastal Kenya - Munguti, Florence Mutave; Nyaboga, Evans Nyaega; Kilalo, Dora Chao; Yegon, Hillary Kipkoech; Macharia, Isaac; Mwango'mbe, Agnes Wakesho (Frontiers in Sustainable Food Systems, 2023)
Cassava productivity is threatened by viral diseases which have become the main phytosanitary problems in cassava farmers. Cassava brown streak disease (CBSD) is a devastating viral disease caused by Cassava brown streak virus (CBSV) and Ugandan cassava brown streak virus (UCBSV) which are transmitted by whitefly vectors and mainly disseminated through the use of infected stem cuttings as planting materials. The aim of the current study was to: (1) assess farmers’ knowledge, perceptions on spread, causes and current management practices of CBSD; (2) determine the factors associated with farmers’ satisfaction with cassava planting material; and (3) determine the distribution, incidence, and severity of CBSD and association of factors influencing the disease epidemics in smallholder cassava cropping systems in coastal Kenya. Information was collected using semi-structured questionnaire administered to 250 smallholder farmers through face-to-face interviews coupled with field visits to assess the incidence, severity and distribution of CBSD. Symptomatic and asymptomatic cassava leaf samples were collected for reverse transcription-polymerase chain reaction (RT-PCR) analysis of the causal viruses of CBSD. The results revealed that majority of the farmers (96.6%) could recognize CBSD symptoms on the roots, and only 11.5 % could recognize the foliar symptoms of the disease. The cause of the disease was unknown to the farmers, with no effective management methods available to them. Majority of farmers (82.5%) recycled own cassava cuttings from previous season’s crop as planting material followed by exchanging/borrowing from neighbors (67.5%). The field incidence of CBSD was highest in Kilifi (27.9%) followed by Kwale (24.7%) and Taita Taveta (10.8%), with severities ranging from 2 to 3 in the three Counties. RT-PCR analysis indicated that 91% of the symptomatic samples tested positive for either of the two viruses occurring either singly or as dual infection. Approximately 3.2% of the asymptomatic samples tested positive for only CBSV. Findings from this study demonstrates the need for awareness creation of farmers on the causes, spread and management practices to control CBSD and the importance of strengthening certified cassava seed systems to reduce the impact of the disease. The study provides base-line information imperative for development of management strategies of CBSD.